A CONFLICT OF LOVE IN JANE AUSTEN'S SENSE AND SENSIBILITY: A MARXIST APPROACH - LATHIFAHANUM , MUANNISA (2007)
This research analyzes a conflict of love reflected in Jane Austen's Sense and Sensibility, based on the Marxist Approach. The object of this research is novel Sense and Sensibility, which is giving emphasis on the major characters especially Elinor and Marianne. This research analyzes the novel in terms of its structural elements and to identify the relation between the novel and the social realities of the English society in the early nineteenth century. This research belongs to qualitative research. In this research, the writer uses two data sources namely primary and secondary data sources. The primary data source is the novel Sense and Sensibility itself; meanwhile the secondary one is other sources that are related to this research. This data is collected by means of documentation and it is analyzed based on Marxist perspective. Based on the analysis, the writer draws some conclusions. First, Austen tries to explore the balance between social and materialistic life. Wealthy is not the most important thing in having happiness. Happiness is an important thing in human's life supported by faithfulness and trust worthy. Second, in Marxist perspective, Jane Austen criticizes the social condition, why there must be any different classes in the society. Marriage is the solution that happens between the two different classes. The marriage will erase the social classes, because the rank between man and woman, bourgeoisie and proletariat become equal after the marriage happens.